Fatigue Properties of Plain Concrete under Triaxial Tension-Compression-Compression Cyclic Loading - Dongfu Zhao; Haijing Gao; Huixuan Liu; Penghe Jia; Jianhui Yang (Shock and Vibration)
Fatigue tests were performed on plain concrete under triaxial tension-compression-compression (T-C-C) cyclic loading with constant and variable amplitude using a large multiaxial machine. Experimental results show that, under constant amplitude fatigue loads, the development of residual strain in the fatigue loading direction depends mostly on the lateral compressive stress ratio and is nearly independent of stress level. Under variable amplitude fatigue loads, the fatigue residual strain is related to the relative fatigue cycle and lateral compressive stress ratio but has little relationship with the loading process. To model this system, the relative residual strain was defined as the damage variant. Damage evolutions for plain concrete were established. In addition, fatigue damage analysis and predictions of fatigue remaining life were conducted. This work provides a reference for multistage fatigue testing and fatigue damage evaluation of plain concrete under multiaxial loads.